Clinical implications of fracture severity risk with pioglitazone: a systematic review and meta-analysis of clinical randomized trials - Azhari, Hala F.; Dawson, Jesse (Frontiers in Pharmacology, 2025)
IntroductionPioglitazone, a thiazolidinedione, effectively reduces stroke and cardiovascular events in individuals with type 2 diabetes, insulin resistance, and/or stroke. However, its potential to increase fracture risk, particularly among women and those with pre-existing skeletal conditions, has not yet been completely understood. This meta-analysis aims to clarify fracture risk associated with pioglitazone, thereby focusing on individuals with a history of stroke.MethodsA systematic review was performed for clinical trials conducted up to March 2024, focusing on trials comparing pioglitazone to placebo or other antihyperglycemic drugs that reported fracture outcomes.ResultsFrom 860 trials identified, 78 satisfied the inclusion criteria: 34 with a high risk of bias, 8 with unclear risk, and 36 with low risk. The meta-analysis revealed an association between pioglitazone and a significant increase in fracture risk (risk ratio [RR] 1.21; 95% CI 1.01–1.45; P = 0.04), including non-serious (RR 1.25; 95% CI 1.03–1.51; P = 0.02) and serious fractures (RR 1.48; 95% CI 1.10–1.98; P = 0.01). Notably, the risk was exacerbated for low-energy fractures, particularly resulting from falls (RR 1.49; 95% CI 1.20–1.87; P = 0.0004), in insulin resistance individuals (RR 0.87; 95% CI 0.43–1.76; P = 0.69), and stroke survivors (RR 1.41; 95% CI 1.09–1.83; P = 0.008). Fractures were most frequently observed in lower extremities (RR 1.85; 95% CI 1.33–2.56; P = 0.0002), with women at a greater risk (RR 1.56; 95% CI 1.20–2.02; P = 0.0008). When compared with other antihyperglycemic drugs, no significant difference in fracture risk was noted (RR 1.08; 95% CI 0.73–1.59; P = 0.70), except rosiglitazone, which showed higher fracture risk (RR 1.42; 95% CI 1.23–1.64; P < 0.00001). Fracture risk was significant in the fixed-effect model but not in the random-effects model.DiscussionThough pioglitazone offers several cardiovascular benefits, its association with increased fracture risk, especially among women and non-diabetic individuals post-stroke, warrants careful consideration. Individualized treatment interventions balancing cardiovascular and skeletal outcomes are essential, and further research is needed to optimize therapeutic strategies in this population.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD42016038242, identifier CRD42016038242.